2007
DOI: 10.1002/jcla.20142
|View full text |Cite
|
Sign up to set email alerts
|

Stromal cell‐derived factor‐1 chemokine gene variant in blood donors and chronic myelogenous leukemia patients

Abstract: Chronic myelogenous leukemia (CML) is a malignant myeloproliferative disorder that originates from a pluripotent stem cell expressing the bcr-abl oncogene. It is characterized by an abnormal release of the expanded, malignant stem cell clone from the bone marrow into the circulation. The stromal cell derived factor-1 (SDF-1) gene contains a common polymorphism, termed SDF1-3'A, in an evolutionarily conserved segment of the 3' untranslated region (UTR). In this work the SDF-1 genotypes of 25 patients (9-82 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
24
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 25 publications
6
24
1
Order By: Relevance
“…Previous studies have shown that a variety of morphological and functional abnormalities exist in the leukemia bone marrow microenvironment, including significantly increased microvascular density, increased expression of some vascular-related growth factors such as VEGF, and some chemokines such as SDF-1 (10,13,14). The disturbance of the leukemia bone marrow microenvironment could promote the production of abnormal adhesion molecules and chemokines, which in turn could promote the adhesion and colonization of leukemia cells to the "niches" of the local microenvironment, thus allowing the leukemia cells to evade chemotherapy through the shielding role of the local hematopoietic matrix.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that a variety of morphological and functional abnormalities exist in the leukemia bone marrow microenvironment, including significantly increased microvascular density, increased expression of some vascular-related growth factors such as VEGF, and some chemokines such as SDF-1 (10,13,14). The disturbance of the leukemia bone marrow microenvironment could promote the production of abnormal adhesion molecules and chemokines, which in turn could promote the adhesion and colonization of leukemia cells to the "niches" of the local microenvironment, thus allowing the leukemia cells to evade chemotherapy through the shielding role of the local hematopoietic matrix.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, the CXCL12-801A allelic variant has been associated with a higher incidence of breast and lung cancer, acute myeloid leukemia, lymphoma and chronic myeloproliferative disease, and with a slower progression to AIDS. 31,[34][35][36][37][38] An interaction between CXCL12 and CXCR4 is critical for the trafficking of hematopoietic progenitor cells in the BM, and an interruption of this interaction can affect…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that polymorphisms in regulatory regions of cytokine genes could affect transcription, resulting in variations of cytokine protein production. Recently, the association between cytokine genes and leukemias has been examined intensively (Bidwell et al, 2001;De Oliveira, 2007).…”
Section: Introductionmentioning
confidence: 99%